Pengaruh Penggunaan Media Sosial Tiktok Terhadap Kualitas Belajar Anak Di Kelas 4 SDN 09 Cibiru - Nuraeni , Eva; Undayasari, Dwi (Elementary Journal : Jurnal Pendidikan Guru Sekolah Dasar, 2025)
The rapid advancement of information technology has significantly influenced human life, particularly through the rise of social media platforms. Among elementary school students, TikTok stands out as one of the most widely used applications, offering a range of content from entertainment to educational videos. However, concerns have emerged regarding its impact on students’ learning quality, especially due to high usage frequency and the prevalence of non-educational content. This study aims to explore the multifaceted effects of TikTok usage—including frequency, duration, content type, and usage timing—on students’ academic performance. The goal is also to highlight the importance of self-regulation and digital literacy among students in using TikTok productively to support better learning outcomes. A qualitative research design was applied, using interviews, questionnaires, and documentation involving 25 fourth-grade students. The findings indicate that students who spend more than four hours per day on TikTok and primarily watch entertainment content tend to perform lower academically. In contrast, students who limit their usage and focus on educational content display stronger motivation and higher academic achievement. The time of use also plays a critical role, as accessing TikTok during study hours or late at night negatively affects students’ concentration and sleep. The study concludes that digital supervision and awareness are essential in guiding students toward healthier media habits. Integrating more educational content into TikTok could enhance its value as a learning tool. These findings contribute to the growing discourse on digital education and offer practical insights for parents and teachers.